Progress Report on the Activities of the Independent Evaluation Office. (Policy Papers; Policy Paper ;, 2009)
The recent developments in the world economy pose many questions regarding the role of the Fund in surveillance and crisis prevention. In view of this, the IEO will be launching an evaluation of how well the Fund performed in the run-up to this crisis. Launching of this study was discussed at a recent meeting of the Evaluation Committee of the Executive Board. Work on this study will start in the coming weeks, and a draft Issues Paper will be issued before the next IMFC meeting.